PERAN HORMON PERTUMBUHAN DALAM PERCEPATAN PROSES AGING - Filda Vionita Irene De Lima (PAMERI, 2023)
Aging is a process that must be experienced by living things, including humans, which causes a decrease in bodily functions. Various theories of aging show the interference of the body's regulatory system from upstream to downstream. One of the regulations that influence is hormonal regulation which is played by growth hormone. Various literature studies show that growth hormone accelerates the aging process. The primary mechanism involves reducing the formation of endogenous antioxidants due to insulin-like growth factor I (IGF-1) activity and decreased metabolic activity regulated by mammalian target of rapamycin (mTOR).